2021
DOI: 10.1186/s12909-021-02782-w
|View full text |Cite
|
Sign up to set email alerts
|

Teaching scripts via smartphone app facilitate resident-led teaching of medical students

Abstract: Background Previous studies have suggested that resident physicians are the most meaningful teachers during the clinical clerkships of third-year medical students (MS3s). Unfortunately, residents often feel unprepared for this crucial role. The pediatrics clerkship at our institution identified a paucity in the frequency of resident-led teaching with MS3s. Lack of confidence, suboptimal teaching space, and insufficient time were cited as the most significant barriers. To enhance resident-led te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry. Student perceptions revealed that applications were an effective and innovative tool for learning during the COVID‐19 period, based on previous trials of smartphone use 41–46 . Furthermore, regarding the perception of students about the use of smartphone applications in this study all students agreed that the applications were valuable, useful (75%), easy to use (50%), and innovative (63%), and improved their skills to answer quizzes and exams (81%).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry. Student perceptions revealed that applications were an effective and innovative tool for learning during the COVID‐19 period, based on previous trials of smartphone use 41–46 . Furthermore, regarding the perception of students about the use of smartphone applications in this study all students agreed that the applications were valuable, useful (75%), easy to use (50%), and innovative (63%), and improved their skills to answer quizzes and exams (81%).…”
Section: Discussionmentioning
confidence: 63%
“…Student perceptions revealed that applications were an effective and innovative tool for learning during the COVID-19 period, based on previous trials of smartphone use. [41][42][43][44][45][46] Furthermore, regarding the perception of students about the use of smartphone applications in this study all students agreed that the applications were valuable, useful (75%), easy to use (50%), and innovative (63%), and improved their skills to answer quizzes and exams (81%). In the same aspect of our study, smartphones could be used to promote skills for different contexts.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous fields of education have widely used computer devices and mobile applications. Some studies have indicated the improvement of the learning experience through various forms of technology, such as digital handbook apps, mobile learning, computer device, and gamification [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It makes teaching methods more varied, reduces learning boredom, and then students become more active. Many fields use Android applications, including education, agriculture, language, economics, marine, and health [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation